Strategi Pemasaran Media Sosial Untuk Meningkatkan Penjualan Bibit Ikan Mas - Ferdi Ardiansyah; Yogi Nofiyandi; Hafidz Fachri Akbar; Rafi Reza Annaufal; Faris Widiyanto; Muhammad Kosim (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2022)
This community service activity was carried out with the aim of assisting goldfish farming entrepreneurs in increasing sales effectiveness through the implementation of social media-based marketing strategies. The main problems faced by entrepreneurs are limited access to a wider market and a lack of knowledge and skills in digital marketing. This results in the cultivation products not being optimally absorbed by the market, resulting in low business revenue. To address these problems, interventions were carried out in the form of education and training on digital marketing strategies, particularly the use of social media as a promotional tool. The implementation methods included counseling, technical training, direct mentoring, and evaluation of the implementation of social media such as Instagram, Facebook, and WhatsApp. Training materials covered the creation of attractive promotional content, copywriting techniques, utilization of social media features, and strategies for increasing audience reach and engagement. The results of the activity showed an increase in participants' understanding of the basic concepts of digital marketing, as well as their ability to manage social media accounts to support goldfish product promotional activities. In addition, an increase in customer interaction (engagement) and an increase in the number of sales transactions through digital platforms were observed after the marketing strategy was consistently implemented. Another positive impact was the growth of entrepreneurs' confidence to expand their market reach independently. This activity makes a real contribution to empowering MSMEs in the fisheries sector to adapt to technological developments and the challenges of the digital era. It is hoped that this empowerment model can be replicated in other small business sectors to support information technology-based local economic growth.